Evaluasi Kegiatan Cetak Sawah pada Kampung Linggua Distrik Mambioman Bapai Kabupaten Mappi - Deliana Mangisu; Alfian Chandra; Davy Jansen; Rahmat Rahmat; Valan Valan (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
Food sovereignty is one of the main programs of the Indonesian government at this time. Food sovereignty must start from gradual food self-sufficiency followed by an increase in the added value of agricultural businesses that are widely used to improve the welfare of farmers. Some of the obstacles include land status, land to be printed is recorded as a forest area, water sources do not yet have adequate irrigation networks. The purpose of this service is to evaluate the achievement of the rice field printing program, analyze obstacles in achieving the program to re-optimize rice field printing land. The methods used are the Survey Preparation Stage, Survey Stage, Investigation Stage and Evaluation Stage and Report Preparation. The results obtained are: the rice field printing program only reached 10 hectares of the expected 200 hectares or only reached 5%, so real follow-up action is needed from the recommended steps, namely: increasing PPL, improving irrigation networks, adding facilities and infrastructure, and rice fields are used as secondary crops. Although there are obstacles faced, they can be resolved well.